Mennyei Falatok . Heavenly Bites - Naszódi, Katalin (Hungary, 2005)
Verzio FF submission Duration: 00:14:00 In 1980 Bertalan Farkas flew to space with the Soviet Interkosmos program. What did they eat during the expedition? How do they make space food? How much money did the Hungarian government spend on this food? How did Unicum get to space? The film not only confides us to the culinary secrets of space cuisine, but also sheds light upon the most outstanding PR event of the Eastern Bloc in 1980. A glimpse at Soviet propaganda via space food.